O amor em mal-estar : a insustentável leveza da domideologia - Francisco, Augusto César (2010)
The discourse about love, in the Western modern world, is an effect of the power that constructs bodies that matter, paraphrasing Butler, which represents a performative reiterarion of the domination drive, forming and ego of love through the imposition of a cultural super-ego. The domination, a real process of social constraint, is concomitant to its ideological secret, which lead us to the expression domideology , inspired by Sousa Filho, to determine the unconscious domination of the ideological discourse, Through a critical analysis of the bases of Freudian discourse about love, we question, inspired by Foucault, the sexual nature of the drive, to put it in a place insecure of critics to the substance metaphysics expression used by Nietzsche. In our point of view, the domination drive is a critical tool for the individual to think about, as interpellated by the love domideology , making believe the only interpretation of the social interchange is love, nuclear element of our modern Western love complex